Where Are the English Learners and Students With Disabilities in Gifted Education? - Scott J. Peters; Angela Johnson (SAGE Publishing, 2024)
Prior research documented disproportional representation across racial, ethnic, and socioeconomic lines within the population of students identified as gifted and talented (GT). Less research has focused on what predicts improved representation for English learners (ELs) or students with disabilities (SwDs), or how state GT policies facilitate such representation. This paper attempted to fill that void by analyzing data from the Civil Rights Data Collection and Stanford Education Data Archive along with original coding of state GT policies. We found that while ELs and SwDs are disproportionately underrepresented within the population of students identified as gifted, state mandates for schools to offer GT, requirements for formal gifted education plans, and regular audits for compliance were correlated with higher rates of GT service availability and greater representation among ELs and SwDs. We further describe the characteristics of the top 5% of schools with the highest GT representation for ELs and SwDs.